Ethical Challenges of Germline Genetic Enhancement - Macpherson, Ignacio; Roqué, María Victoria; Segarra, Ignacio (Frontiers in Genetics, 2019)
The new reproductive technologies have opened the door to different processes of genetic enhancement, by which the characteristics of an individual could be selected during its gestation, according to the interests of the agents involved. Although the initiative is apparently oriented towards developing individuals that would excel in society, critical voices raise the concerns that this approach would generate upon a reflection on the ethical, social and legal implications of these techniques and their implementation in society. We have reviewed the literature about these issues throughout their historical records to date, focusing on the moral arguments and non-clinical aspects that affect the legal and social environment. We have observed various trends and currents of thought with divergent positions (proactive, preventive and regulatory) as well as a large number of articles that try to reconcile the different approaches. The review illustrates a series of concepts from the ethics and philosophy fields which are frequently used in studies that evaluate the ethical implications of genetic enhancement, such as dignity, benefit, autonomy and identity. In addition, amongst the main unresolved controversies related to genetic enhancement, we may highlight procreative beneficence, genetic disassociation, gender eugenics, the value of disability, embryo chimerization and the psychosocial inequality of potentially enhanced individuals. We also develop possible scenarios for future debate. We consider especially important the definition and specification of three aspects which understanding may be essential upon the deployment of new reproductive/procreation technologies: the moral status of the embryo upon his/her enhancement, the legal status of the enhanced individual and the responsibility of the agents executing the enhancement.